Investigating The Impact Of Live Streaming Product Display And Streamer Engagement On Purchase Intention With Hedonic Motivation As A Moderator - Hiasintus Ody Nusatara; MG Westri Kekalih Susilowati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Live streaming has been one of the most up-to-date digital marketing strategies, enabling direct interaction between sellers and consumers. This study analyzes the influence of live streaming product display and streamer engagement on purchase intention, considering hedonic hedonic motivation as a moderating variabel. The quantitative method using Partial Least Squares-Structural Equation Modeling (PLS-SEM) was employed in this research, with 159 respondents, most of whom were university students in Semarang City. These findings indicate that the live streaming of product display and streamer engagement are strong drivers of purchase intention. Hedonic motivation can moderates the relationship between streamer engagement and purchase intention but does not quite moderate the realtionship between livestreaming product display and purchase intention. The contribution this study makes to the literature purpose that interactiion between streamers and customers is much more important than mere visual ecposure to product. These findings provide insight for marketers to optimize live live streaming strategies in order to enhance consumer purchase intention.